View of the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
The Hanuman Garhi temple complex is the largest complex among the structures at Arthuna. It consists of two main temples: the Neelkanth Mahadev and the Hanuman temples. Both are living shrines, along with over a dozen of smaller temples. There are also memorial stones and small shrines in this complex. The complex originally had an entrance from the eastern side. Neelkanth Mahadev temple has a shekhari (multi-spire) style shikhara (superstructure) and Shiva temple with Phamsana (stepped pyramidical) shikhara has sculptures on its walls.